Analysis of sleep apnea research with a special focus on the use of positron emission tomography as a study tool - Li, Anting; Jaakkola, Maria; Saaresranta, Tarja; Klén, Riku; Li, Xiang-Guo (Elsevier, 2025)
The quality of sleep plays a significant role in determining human well-being, and studying sleep and sleep disorders using various methods can aid in the prevention and treatment of diseases. Positron emission tomography (PET) is a noninvasive and highly sensitive medical imaging technique that has been widely adopted in the clinic. This review article provides data on research activity related to sleep and sleep apnea and discusses the use of PET in investigating sleep apnea and other sleep disorders. We conducted a statistical analysis of the number of original research articles published on sleep and sleep apnea between 1965 and 2021 and found that there has been a dramatic increase in publications since 1990. The distribution of contributing countries and regions has also undergone significant changes. Although there is an extensive body of literature on sleep research (256,399 original research articles during 1965–2021), PET has only been used in 54 of these published studies, indicating a largely untapped area of research. Nonetheless, PET is a useful tool for identifying connections between sleep disorders and pathological changes in various diseases, including neurological, metabolic, and cardiovascular disorders, as well as cancer. To facilitate the broader use of PET in sleep apnea research, further studies are needed in both clinical and preclinical settings.